HUBUNGAN BEBAN KERJA PERAWAT DENGAN BURNOUT SYNDROME DI RUMAH SAKIT UMUM DAERAH KOTA KUPANG - Novita Ivan Ton (CHMK HEALTH JOURNAL, 2019)
Big part of worker in hospital is nurse. Work burden is total kind of jobs that must be finished by health professional worker like nurse. Burnout syndrome is decrease of physic and mental power totally caused by job. The purpose of this research is to identify the relationship between nurse work burden and burnout syndrome in public hospital of Kupang city. Research design is correlation study by cross sectional approach and sampling used is nonprobability sampling by quota sampling way. Total respondents in this research were 51 men. Instrument used was questionnaire. Chi- square test result is p significant = 0,831 > 0, 05. Result of X ² count (2,278) ≤ X ² table (9,488) it means that HO received means that there is no significant between nurse work burden and burnout syndrome. But it suggested to nurse in public hospital of Kupang city to wary to burnout symptom so that symptom did not appear into burnout condition by creating good relation, enjoyable situation and cooperative between work partner and do not take out the risk work that cannot handle and to arrange time to relax every day. Key words: nurse work burden and burnout syndrome.